Influence of on-the-tree fruit bagging on biotic stresses and postharvest quality of rainy-season crop of 'Allahabad Safeda' guava (Psidium guajava L.). (September 2020) - Sharma, R.R.; Nagaraja, A.; Goswami, A.K.; Thakre, Madhubala; Kumar, Raju; Varghese, Eldho
Abstract: In India, guava trees produce two crops per year, one in the rainy-season and another in the winter. The rainy-season crop is severely infested by fruit fly, anthracnose disease and birds. Because of low quality, the rainy-season crop is usually discarded by farmers. In recent years, on-the-tree fruit bagging has emerged as one of the most effective approaches for controlling pests and diseases and quality improvement in fruits. Hence, we attempted to observe the effects of five different types of bags on the rainy-season crop of 'Allahabad Safeda' guava. For this, fruits were covered with either of four types of bags (nylon nets, polypropylene (PP) non-woven, butter paper and brown paper) at marble stage of development during the rainy-season crop for two consecutive years. All bags significantly advanced fruit maturity and improved fruit weight, texture, visual appeal, quality, and functional attributes over unbagged (control) fruits. Interestingly, fruit bagging with PP non-woven bags significantly reduced fruit drop and provided complete control of fruit fly, anthracnose and bird damage compared to unbagged fruits that suffered high incidence of fruit fly (56.6 ± 1.08%), anthracnose (6.6 ± 0.27%) and bird damage (14.6 ± 0.23%). Thus, it can be concluded that on-the-tree fruit bagging with PP non-woven bags is useful for controlling major pest and/or disease and improving fruit quality of the rainy-season guava crop. Highlights: All bagging treatments reduced the incidence of fruit fly, anthracnose and bird damage but PP non-woven bag was the best. The functional attributes and fruit quality of winter guava was the best in PP non-woven bags. The PP non-wven bags enhanced the maturity of guava fruits by about ten days.